5‐Hydroxymethylcytosine signature in circulating cell‐free DNA as a potential diagnostic factor for early‐stage colorectal cancer and precancerous adenoma. Issue 1 (14th November 2020) - Xiao, ZeWen; Wu, Wendy; Wu, Chunlong; Li, Man; Sun, Fuming; Zheng, Lu; Liu, Gaojing; Li, Xiaoling; Yun, Zhiyuan; Tang, Jiebing; Yu, Yang; Luo, Shengnan; et al.
Abstract : Approximately 85% colorectal cancers (CRCs) are thought to evolve through the adenoma‐to‐carcinoma sequence associated with specific molecular alterations, including the 5‐hydroxymethylcytosine (5hmC) signature in circulating cell‐free DNA (cfDNA). To explore colorectal disease progression and evaluate the use of cfDNA as a potential diagnostic factor for CRC screening, here, we performed genome‐wide 5hmC profiling in plasma cfDNA and tissue genomic DNA (gDNA) acquired from 101 samples (63 plasma and 38 tissues), collected from 21 early‐stage CRC patients, 21 AD patients, and 21 healthy controls (HC). The gDNA and cfDNA 5hmC signatures identified in gene bodies and promoter regions in CRC and AD groups were compared with those in HC group. All the differential 5hmC‐modified regions (DhMRs) were gathered into four clusters: Disease‐enriched, AD‐enriched, Disease‐lost, and AD‐lost, with no overlap. AD‐related clusters, AD‐enriched and AD‐lost, displayed the unique 5hmC signals in AD patients. Disease‐enriched and Disease‐lost clusters indicated the general 5hmC changes when colorectal lesions occurred. Cancer patients with a confirmable adenoma history segmentally gathered in AD‐enriched clusters. KEGG functional enrichment and GO analyses determined distinct differential 5hmC‐modified profiles in cfDNA of HC individuals, AD, and CRC patients. All patients had comprehensive 5hmC signatures where Disease‐enriched and Disease‐lost DhMR clusters demonstrated similar epigenetic modifications, while AD‐enriched and AD‐lost DhMR clusters indicated complicated subpopulations in adenoma. Analysis of CRC patients with adenoma history showed exclusive 5hmC‐gain characteristics, consistent with the 'parallel' evolution hypothesis in adenoma, either developed through the adenoma‐to‐carcinoma sequence or not. These findings deepen our understanding of colorectal disease and suggest that the 5hmC modifications of different pathological subtypes (cancer patients with or without adenoma history) could be used to screen early‐stage CRC and assess adenoma malignancy with large‐scale follow‐up studies in the future. Abstract : Genome‐wide 5hmC profiling in cell‐free DNA acquired from CRC patients, adenoma patients, and healthy individuals revealed that the differential 5hmC‐modified regions were gathered into four clusters with no overlap, although there are a few overlapped genes shared between the different clusters. CRC patients with adenoma history showed exclusive 5hmC‐gain characteristics, which was consistent with the 'parallel' evolution hypothesis in adenoma.